Human Rights and Natural Law An Intercultural Philosophical Perspective - Schweidler, Walter (Academia Press, 2012)
It was in ancient Greek philosophy where the idea arose that there is a supreme law before which any civil law created by human societies has to be justified. Since then the concept of natural law not only remained one of the paradigms of Western civilization but has shaped the development of international legislation in general. The understanding of the significance of the idea of a natural law for the philosophical presuppositions of our current concepts of human rights and human dignity is still dependent on the analysis of its relation to the different cultures and civilizations on earth.